2022
DOI: 10.1083/jcb.202009037
|View full text |Cite
|
Sign up to set email alerts
|

Tricellulin secures the epithelial barrier at tricellular junctions by interacting with actomyosin

Abstract: The epithelial cell sheet functions as a barrier to prevent invasion of pathogens. It is necessary to eliminate intercellular gaps not only at bicellular junctions, but also at tricellular contacts, where three cells meet, to maintain epithelial barrier function. To that end, tight junctions between adjacent cells must associate as closely as possible, particularly at tricellular contacts. Tricellulin is an integral component of tricellular tight junctions (tTJs), but the molecular mechanism of its contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 55 publications
(79 reference statements)
1
33
0
Order By: Relevance
“…22 In the present manuscript, we also examined the roles of C-terminal cytoplasmic tails of OCLN and TRIC, which have been implicated in the localization and function. 32,33,39,40,58,59,60 The mutant TRIC lacking the C-terminal cytoplasmic tail was localized at bicellular TJs (and lateral membranes) and restored the paracellular barrier of the Tric/Ocln-dKO cells (Figures 5B, 6, and Figure S6). This suggests that the C-terminal cytoplasmic tail of TRIC is not required to maintain the barrier function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…22 In the present manuscript, we also examined the roles of C-terminal cytoplasmic tails of OCLN and TRIC, which have been implicated in the localization and function. 32,33,39,40,58,59,60 The mutant TRIC lacking the C-terminal cytoplasmic tail was localized at bicellular TJs (and lateral membranes) and restored the paracellular barrier of the Tric/Ocln-dKO cells (Figures 5B, 6, and Figure S6). This suggests that the C-terminal cytoplasmic tail of TRIC is not required to maintain the barrier function.…”
Section: Discussionmentioning
confidence: 94%
“…39 In addition, the Cterminal tail of TRIC binds to angulins and α-catenin. [40][41][42] knockin mice carrying a truncated TRIC lacking the OCEL domain exhibited a similar phenotype of TRIC-deficient mice and suffered from early onset progressive hearing loss, suggesting that this region plays a pivotal role in the inner ear cells. 43,44 Although it was reported that the C-terminal tails of both OCLN and TRIC are essential for their proper localization, 32,44 their roles in the regulation of the structure and function of TJs are not yet fully understood.…”
Section: Introductionmentioning
confidence: 91%
“…In this issue, Cho and colleagues ( 5 ) set out to discover the molecular mechanism that maintains junctional integrity at vertebrate TCJs. Previously, partial loss of tricellulin was shown to impair tTJ organization and epithelial barrier function ( 1 ).…”
mentioning
confidence: 99%
“…Previous work proposed that the organization of actomyosin at TCJs might be important for generating a tightening force for sealing tTJs ( 7 ). Using a calcium switch assay, Cho et al ( 5 ) demonstrated that during TCJ formation, actin filaments form a crisscrossing meshwork at TCJs, and myosin II localizes on overlapping antiparallel actin filaments ( Fig. 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation